Radial stiffness analysis of circular ring with uncertain boundary conditions: Mechanical elastic wheel as an example. (April 2022) - Zhang, Chenxi; Zhao, Youqun; Feng, Shilin; Xu, Han; Wang, Qiuwei; Deng, Huifan
The paper studies the radial stiffness of mechanical elastic wheel (MEW), which is regarded as a circular ring with uncertain boundary conditions for the first time, and proposes a ring-chain model to solve the radial stiffness of the ring. Different from assuming the boundary conditions by experience or building finite element model with complex processes from previous researches, the ring-chain model coupling circular ring model and dynamics of multi-rigid body is accurate and simple to find the loaded positions of ring and make the boundary conditions clear. The results show that the ring-chain model can be solved to get the deformations and loaded positions of ring, the radial stiffness of MEW is large, and the radial displacement of MEW increases non-linearly. The results are consistent with that from finite element model under the same settings, but the time cost of ring-chain model is less. In addition, the influence factors of ring radial stiffness are also found and analyzed. The method presented in this paper can provide data for the response analyses of vehicle and references for the analysis of circular ring with uncertain boundary conditions.